ANALYSIS OF FARMERS’ SATISFACTION ON HYBRID RICE SEED MAPAN P-05 IN PENDEM VILLAGE, JUNREJO SUBDISTRICT, BATU CITY - Sri Wahyuni; Ratya Anindita; Condro Puspo Nugroho (Agricultural Socio-Economics Journal, 2018)
The purpose of this research is to describe the knowledge of farmers about the seed of hybrid rice Mapan P-05, to analyze the conformance of performance and importance level, and to analyze farmers’ satisfaction to hybrid rice seeds of Mapan P-05. Sampling method used is census, where all the population members are farmers who use the seed of Mapan P-05. Methods of data analysis use descriptive analysis and quantitative analysis, which are IPA (Importance Performance Analysis) and CSI (Customer Satisfaction Index). The results found that the conformance level of performance and importance of hybrid rice seed Mapan P-05 is 80.2%; while the level of overall satisfaction is 62.06%. From the CSI, the attributes which should be considered by producers are the price, the seeds productivity, the seeds availability and the harvest age. Mapan P-05